2019
DOI: 10.1088/1742-6596/1341/9/092022
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Firm’s Unique Resource in Developing Sustainable Competitive Advantage from Strategy Inimitability and its Effect on Firm Performance of Mining Companies in Indonesia

Abstract: The positive relationship between unique resources and sustainable competitiveness of the company has been well understood and applies to almost all businesses. However, little is known about the specific effects of the uniqueness of resources and business strategies in this relationship. Using resource-based view (RBV), Porter's five-factor theory, and game theory, as well as imitation theory between companies, this study explains how the influence of company-specific resources and the uniqueness of the compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…This provides evidence that competitive advantage will be able to enhance firm performance. These results are consistent with previous research by Rauf et al (2019). Currently, companies in Indonesia operate in a fairly intense, competitive arena.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This provides evidence that competitive advantage will be able to enhance firm performance. These results are consistent with previous research by Rauf et al (2019). Currently, companies in Indonesia operate in a fairly intense, competitive arena.…”
Section: Discussionsupporting
confidence: 93%
“…Competitive advantage is a company's ability to create investments that are above average (Mee-Ngoen et al, 2020). The company's strategy in terms of gaining competitive advantage that competitors cannot imitate is a means of reducing costs that are too large and this will be able to improve firm performance (Rauf et al, 2019). In a differentiation strategy, companies must create unique and different products that cannot be imitated by competitors, and this will form a competitive advantage for the company and will reduce the company's costs .…”
Section: Hypothesis 1: Green Supply Chain Management Has a Positive E...mentioning
confidence: 99%
“…By implementing environmental management, companies can strengthen competitiveness and create a competitive advantage (Mee-ngoen et al, 2020). The company's strategy in competitive advantage that cannot be imitated by competitors is an attempt to reduce huge costs, that will be able to increase firm performance (Rauf et al, 2019). In a differentiation strategy, the company must create a unique and different product so that it cannot be imitated by competitors, will form a competitive advantage for the company, and decrease the company's costs (Khan et al, 2019).…”
mentioning
confidence: 99%
“…In this instance, a firm's getting the resources it didn't have in the past, can bring in a competitive advantage. Rauf, Kadir and Kamariah (2019) reported that sustainable competitive advantages are tough to replicate or duplicate. Competitive advantage is a base or an essence for creating strategy, and developing strategy are to develop and maintain a competitive advantage under the firm's goals.…”
Section: Background Of the Studymentioning
confidence: 99%